Case Report: Male Lobular Breast Cancer in Hereditary Cancer Syndromes - Carnevali, Ileana; Tedaldi, Gianluca; Pensotti, Valeria; Sahnane, Nora; Micello, Donata; Rovera, Francesca; Sessa, Fausto; Tibiletti, Maria Grazia (Frontiers in Oncology, 2022)
BACKGROUND Lobular breast carcinoma (LBC) is exceptionally considered a rare disease in men, including only 1% of all male breast malignancies. The majority of LBCs have negative immunohistochemical staining for E-cadherin (CDH1) expression and loss of CDH1 function was traditionally implicated in the tumorigenesis of diffuse gastric cancer as well as LBC. It is well recognized that LBC in women could be involved in both Hereditary Breast and Ovarian Cancer (HBOC) and Hereditary Diffuse Gastric Cancer (HDGC) syndromes, however, no data are present in literature about the involvement of male LBC in these inherited conditions. METHODS BRCA1, BRCA2 and CDH1 genes germline analyses were performed on DNA from peripheral blood using Next-Generation Sequencing (NGS), Sanger sequencing and Multiplex Ligation-dependent Probe Amplification (MLPA) analyses. BRCA2 and CDH1 Somatic genes analyses were performed on breast tumoral DNA using NGS sequencing approach. RESULTS and CONCLUSIONS Here we describe two males affected by LBC, carriers of a pathogenic variant of BRCA2 and CDH1 genes, respectively. Our data, including somatic and germline results, demonstrate a strong relationship between male LBC and HBOC/HDGC syndromes excluding a sporadic origin of LBC in these two patients. Male LBC could represent a sentinel cancer for inherited syndrome identification and the early identification of cancer susceptibility could improve cancer prevention both for males and females in these families. The history of LBC patient carrier of CDH1 variant suggests to include male LBC genetic testing criteria and male breast surveillance in HDGC guidelines.